The Effectiveness of Phonics Approach in Teaching Reading - Atika Salman Faris (Universitas Muhammadiyah Mataram, 2018)
This research aimed to determine the effectiveness of phonics approach in teaching reading for the seventh graders of SMP Negeri 1 Aikmel, East Lombok, and to what extent it is effective. This research was designed as pre-experimental with read aloud test as the instrument to collect data. The sample of this research consisted of 36 students of SMP Negeri 1 Aikmel. The sample was taken through purposive sampling. In collecting the data, a pre-test and a post-test were given to the students. SPSS 17 for Windows and paired-sample t-test were applied to analyze the collected data. After, calculating the data, it could be known that there was a significant difference in the mean scores between pre-test and post-test, t(df=35) = 23.314 at p = 0.001, meaning that the null hypothesis was rejected and the alternative hypothesis was accepted. In a nutshell, phonics approach was significantly effective in teaching reading for the seventh graders of SMP Negeri 1 Aikmel.